Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 10 - Section 10.1 - Sequences and Summation Notation - Exercise Set - Page 1051: 99



Work Step by Step

Need to check the formula. $\sum_{ i=1}^ 2(-1) ^i 2^i=0$ Then, $\sum_{ i=1}^ 2(-1) ^i 2^i=(-1)^1 \cdot 2^1+(-1)^2 \cdot 2^2=2$ But $2 \neq 0$ This implies that $\sum_{ i=1}^ 2(-1) ^i 2^i \neq 0$ Hence, the statement is false.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.